Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Grindak Artha Prima Tangerang Selatan - Liyana Hadi; Retno Japanis Permatasari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the simultaneous influence of motivation and work discipline on employee performance at PT. Grindak Artha Prima, South Tangerang. The method used is quantitative associative. The research population was 60 people and all of them were the sample in this study. The data analysis techniques used are instrument testing, classical assumption testing, descriptive analysis, egression testing, correlation coefficient testing, coefficient of determination testing and hypothesis testing. The results of this research show that motivation partially influences employee performance by 42,4%, while 57,6% is influenced by other variables that were not studied. Work discipline partially influences employee performance by 60,3%, while 39,7% is influenced by other variables not studied. Motivation and work discipline simultaneously influence employee performance by 66.9%, while 33,1% are influenced by other variables not studied. The results of the research show the multiple linear regression equation Y = 4,430 + 0,299 X1 + 0,617 Simultaneously, motivation and work discipline have a positive and significant effect on employee performance, this is proven by the calculated F value > F table, namely (57,620 > 3,16) with a significance of 0,000 < 0,05, so H0 is rejected. H3 is accepted, meaning there is a significant influence. positive and significant relationship between motivation and work discipline on employee performance simultaneously at PT. Grindak Artha Prima, South Tangerang.